2015
DOI: 10.1007/s00213-015-3868-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ceftriaxone on GLT1 isoforms, xCT and associated signaling pathways in P rats exposed to ethanol

Abstract: Rationale Several studies have demonstrated a correlation between extracellular glutamate concentration in the mesolimbic reward pathway and alcohol craving. Extracellular glutamate concentration is regulated by several glutamate transporters. Glial glutamate transporter 1 (GLT1) is one of them that regulates the majority of extracellular glutamate concentration. In addition cystine/glutamate antiporter (xCT) is another transporter that regulates extracellular glutamate. Objectives We focus in this study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 70 publications
13
62
0
Order By: Relevance
“…We did not observe an upregualtory effect on GLAST expression with ampicillin treatment. This effect is in accordance with a recent finding demonstrating that ceftriaxone treatment did not induce an upregulatory effect on GLAST expression [13, 15]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not observe an upregualtory effect on GLAST expression with ampicillin treatment. This effect is in accordance with a recent finding demonstrating that ceftriaxone treatment did not induce an upregulatory effect on GLAST expression [13, 15]. …”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that ceftriaxone-induced attenuation of ethanol intake and relapse-like ethanol drinking in male P rats is associated in part with upregulation of GLT-1 and its isoforms (GLT-1a and GLT-1b) in the NAc and PFC [13, 15, 17, 19]. The upregulatory effects on GLT-1 could be associated with a decrease in extracellular glutamate concentrations leading to the reduction in ethanol intake.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in motor cortex of patients with amyotrophic lateral sclerosis the expression of GLT-1a is downregulated while GLT-1b expression is upregulated (Maragakis et al, 2004). Previous studies from our laboratory have demonstrated that ceftriaxone-induced GLT-1a and GLT-1b expression in NAc and PFC, and this effect was found associated with a significant decrease in continuous ethanol intake and relapse-like ethanol drinking in male P rats (Alhaddad et al, 2014a; Rao et al, 2015b). In order to investigate differential effects on GLT-1a and GLT-1b expression, in this study, we tested the effects of both cefazolin and cefoperazone on GLT-1a and GLT-1b expression in P rats exposed to free choice ethanol (15% and 30%).…”
Section: Introductionmentioning
confidence: 68%
“…Therefore, GLT-1 upregulators are rationalized as potential treatment option for treating alcohol addiction. Following the discovery by Rothstein et al reported β-lactam antibiotics as potent GLT-1 upregulators (Rothstein et al, 2005), we have shown that ceftriaxone, a β-lactam antibiotic, reduced ethanol intake and relapse to ethanol intake presumably by increasing the expression of GLT-1 in the mesocorticolimbic areas of the brain including NAc and PFC (Alhaddad et al, 2014a; Qrunfleh et al, 2013; Rao and Sari, 2014; Rao et al, 2015b). Similarly, other β-lactams, including cefazolin and cefoperazone at dose of 100 mg/kg/day for 5 consecutive days, were found to be effective in reducing ethanol intake in male P rats (Rao et al, 2015a).…”
Section: Introductionmentioning
confidence: 77%
“…Also, recovery of ethanol intake following AMOX and AUG treatment was not assessed, thus it remains to be seen whether the observed effects of these drugs are long-term or if the ethanol intake is only reduced in the presence of the drugs. Finally, it would be important to study the effects of these drugs on sodium independent glutamate uptake since another β-lactam antibiotic, CEF, has also been shown to modulate the expression of the cysteine/glutamate exchanger (xCT) (Rao et al, 2015). …”
Section: Discussionmentioning
confidence: 99%